2007
DOI: 10.1097/gme.0b013e31803816ca
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of reproductive physiology and hormone therapy in 53- to 54-year-old Swedish women

Abstract: Knowledge of reproductive physiology and hormone therapy in 53-to 54-year-old Swedish women: a population-based study., 2007, Menopause, (14) Women with low educational level were more likely to answer the questions by stating that they were unsure than did women with high educational level. Ever users of HT knew more than never-users about risks and benefits of HT in relation to breast cancer and osteoporosis, and ever-users thought that the risks of thrombosis and myocardial infarction were lower than did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
(37 reference statements)
2
6
0
Order By: Relevance
“…Women who had originally started HT in the belief that it would have preventive health effects stopped HT to a greater extent than those who had originally started because they were experiencing symptoms 14 . The reasons for abandoning HT were similar to those found in previous studies: side effects, recommendations from a doctor, fear of cancer, and long term HT 20,26,27 . Li and co-workers reported that background factors such as education and employment contributed to the women's decision to abandon HT or not 27 .…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Women who had originally started HT in the belief that it would have preventive health effects stopped HT to a greater extent than those who had originally started because they were experiencing symptoms 14 . The reasons for abandoning HT were similar to those found in previous studies: side effects, recommendations from a doctor, fear of cancer, and long term HT 20,26,27 . Li and co-workers reported that background factors such as education and employment contributed to the women's decision to abandon HT or not 27 .…”
Section: Discussionsupporting
confidence: 70%
“…Our response rate of 77%, of which we analyzed 73 % after omitting answers with inconsistent results, is in accordance with other previous Swedish questionnaire studies 2,10,20 , and above the recommended minimal response rate of 65% 28 . The method of asking about HT use in several different ways and then excluding the women who answered inconsistently strengthened the study by increasing its internal validity.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…2.0-23.5%) [21,24] and was much lower than that in western countries [25,26,27]. In 126 women with HRT awareness, 74.6% of them thought HRT promoted youth and climacteric symptom relief.…”
Section: Discussionmentioning
confidence: 99%